Research on analytical customer relationship management in China: Knowledge map analysis based on Citespace - Jie, Yang; Binti Makmor, Nurkhalida; Ur Rehman, Asad (Edelweiss Applied Science and Technology, 2024)
With the rapid development of the social economy, customers have become the most critical resources of companies, and many companies have taken analytical customer relationship management (CRM) as the magic weapon to improve their core competitiveness. As the main driving force of global economic growth, China currently occupies an essential position in the worldwide economy. Using CiteSpace information visualization software, this paper quantitatively analyzed the relevant research of 98 Web of Science (WoS) studies and 616 Chinese papers in China National Knowledge Infrastructure (CNKI) from 2003 to 2023 regarding analytical CRM in China. The research results of analytical CRM in China draw a knowledge mapping to sort out the annual publication volume, topic, publishing institution, and keyword. It was found that Chinese scholars have focused on analytical CRM in China during the last 20 years, and it entered a relatively rapid growth period in 2013, forming a relatively complete body of knowledge. However, the overall number of publications in WoS is low, and the research field is narrow. According to the data, foreign scholars’ research has certain limitations, primarily focusing on applying concepts in information technology. The layout between different research topics is scattered and the correlation is low. This paper provides a comprehensive analysis to point out the direction for researchers in the area of analytical CRM to engage in related research, provide data reference, and help to predict the future trend of this research. Future research should fully use big data and information technology and focus on analytical CRM in the network era to help Chinese companies improve their competitiveness.